Development of carbon nanotube-reinforced ultra-high performance concrete - Chua, Yong Nian (2014)
With the aim of developing an Ultra High Performance Concrete (UHPC) with a compressive strength of more than 200MPa, and a tensile force beyond 30MPa, Carbon nanotubes (CNT) were added to investigate the effect of the CNT on the mechanical strength of the UHPC. Various mixes with 2 different kinds of CNT as well as varying concentrations of CNT were experimented and tested. Thereafter, Ground Granulated Blast-Furnace Slag (GGBS) was also used to replace a portion of cement in some mix to establish the influence of GGBS on the mix.